Adaptation and psychometric properties of the academic self-ef icacy scale in the context of clinical simulation - Lermanda Peña, Cristian Felipe.; Astudillo Ganora, Ignacio Alejandro.; Zúñiga Espinoza, Julia. (Universidad de Holguín, 2024)
"In the area of education and training of health professionals, teaching-learning methodologies have been evolving, making clinical simulation a fundamental tool for the development of clinical skills and decision-making in a safe and controlled environment. The objective is to adapt the academic self-efficacy scale previously validated in the Chilean population to the clinical simulation context and subsequently to study the psychometric behavior of this scale. A cross-sectional study was carried out in two stages, in the first one the instrument was adapted to the clinical simulation context, and in the second one, its psychometric properties were evaluated. The scale to measure academic self-efficacy in health students in a simulation context has adequate psychometric properties to be used in the target population. "
Adaptación y propiedades psicométricas de la escala de autoeficacia académica en el contexto de simulación clínica
"Adaptação e propriedades psicométricas da escala de autoeficácia acadêmica no contexto de simulação clínica"
Keywords: Calidad de la educación; Salud